Prioritising factors influencing consumers' reversing intention of e-waste using analytic hierarchy process - Najmi, Arsalan; Kanapathy, Kanagi; Aziz, Azmin Azliza (Inderscience, 2019)
Improper management of electronic waste (e-waste) is becoming a threat globally and emerges as the most recent and dangerous environmental issue that is abruptly affecting ecological and human health. In such scenario, manufacturers need to play their role in accepting responsibility to take care of the waste when they reach their end of life. For said purpose, the present study identified factors by which manufacturer can encourage end-consumers to reverse the products, at their discretion, when it reach end of life. Factors identified from literature were prioritised by using analytic hierarchy process (AHP). Results of the present study will help the manufacturers in devising their strategies for marketing and customer relationship management in a way that they can encourage consumers to reverse the products when it reach end of life. © 2019 Inderscience Enterprises Ltd.